Identifikasi Faktor-Faktor Pengulangan Foto Cervical pada Modalitas Digital Radiography di Rumah Sakit Pusat Pertamina - Dian Mahmudah; Muhammad Adam Pamungkas; Achmad Hasmy; Zamitra Mila Dhea (PT Wahana Global Education, 2026)
Cervical radiographic examinations using Digital Radiography (DR) technology at Pertamina Central Hospital (RSPP) revealed a high repeat rate of 28.79%, significantly exceeding the national tolerance threshold of ≤ 2% set by the Ministry of Health. This study aims to identify the underlying factors contributing to repeated cervical imaging in order to improve service quality and patient safety. Employing a descriptive mixed-method observational design, the research was conducted over two months at the radiology unit of RSPP. The findings indicate that patient positioning errors were the most prevalent cause (19.70%), followed by image artifacts (6.06%) and improper DR cassette placement (3.03%). These technical errors lead to unnecessary radiation exposure, reduced service efficiency, and diminished patient trust. Therefore, the study recommends continuous training for radiology personnel, implementation of pre-examination checklists, and comprehensive patient education as preventive measures to reduce repeat rates and enhance radiology service quality.